Review outcomes of laparoscopic assisted colectomy compared with open colectomy in colorectal surgery at Hospital Universiti Sains Malaysia - Nik Mohd Nurhafizi Nik Anuar
INTRODUCTION Colorectal carcinoma is one of the common malignant neoplasms in this country (Rashid et al. 2009). Minimally invasive surgery in colorectal cancer patients has improved quality of life, however the impact of this development has not been studied in HUSM population. OBJECTIVES To study the epidemiology of colorectal carcinoma in patient admitted to HUSM from January 2007 till December 2013. The primary objective was to evaluate outcomes of laparoscopic assisted colectomy and open colectomy in colorectal cancer in HUSM METHODOLOGY This is a study of retrospective record review of 124 patients diagnosed from 1st January 2007 to 31st December 20013. All patients diagnosed with colorectal malignancy requiring surgery were included in this study. Type of surgery, duration of surgery, duration of hospital stays post operative were surgical free margin were compared between laparoscopic assisted colectomy (LAC) group and open colectomy (OC) group. All these data's were traced from operative notes, patient notes and histopathological reports. RESULTS 124 patients were studied for 7 years period ranging from January 2007 till December 2013. The ratio of patients underwent OC compared to LAC was 2: 1. There was almost equal sex distribution in each group. Majority of patients are Malay. The average age at presentation was 59 in OC and 58 in LAC group. There is no statistically significant difference in duration of operation between LAC and OC method of surgery. The length of hospital stay post operative in LAC group is significantly shorter compared to OC (p< 0.05). The post operative complication and surgical free margin and survival rate have no significant association between methods of surgery. CONCLUSION Laparoscopic assisted colectomy for colorectal cancer is an acceptable alternative to openy. colectomy and proved to be more effective in term of short terms outcomes.